Development of carrot cv. BrasÃlia under fertilization in Nova Xavantina - MT - Barichello, L. A.; Menezes, M; Machado, J. K. L.; Brito, I. A.; Pinheiro, J.; Peter, D. G.; Oliveira, A. C.; Silva, V. L. (Scientific Electronic Archives, 2018)
The carrot ( Daucus carota L. ) is a crop of great importance in the market , but not properly fertilized soils can compromise the production and form deformed roots and unfit for consumption. The objective was to evaluate the growth characteristics and production of carrot cv. Brasilia, subjected to organic manure and mineral fertilizers during the summer period. It analyzed the length of the root, the root basal diameter, shoot length, dry weight and fresh root and shoot carrot. The results were not statistically significant, but the mineral fertilizer, organic and long days of summer period served as positive factors for culture, favoring the root growth in its basal diameter and shoot. It was concluded that organic fertilizers and mineral fertilizers had any influence on cv. Brasilia statistically, but all treatments achieved the expected average of carrot productivity